A low-cost monitor for simultaneous measurement of fine particulate matter and aerosol optical depth - Wendt, Eric, author; Volckens, John, advisor; Jathar, Shantanu, committee member; Yalin, Azer, committee member; Pierce, Jeffrey, committee member (Colorado State University. Libraries, 2018)
Exposure to airborne particulate matter with diameters less than 2.5 µm (PM2.5) is a leading cause of death and disease globally. In addition to affecting health, PM2.5 affects climate and atmospheric visibility. NASA currently uses satellite imaging technology to measure particulate matter air pollution across the world. Satellite image data are used to derive aerosol optical depth (AOD), which is the extinction of light in the atmospheric column. Although AOD data are often used to estimate surface PM2.5 concentration, there is considerable uncertainty associated with the relationship between satellite-derived AOD and ground-level PM2.5. Instruments known as Sun photometers can measure AOD from the Earth's surface and are often used for validation and calibration of satellite data. Reference-grade Sun photometers generally do not have co-located PM2.5 measurements and are too expensive to deploy in large numbers. The objective of this work was to develop an inexpensive and compact integrated PM2.5 mass and AOD sampler known as the Solar-Powered Aerosol Reference Calibrator (SPARC). PM2.5 is sampled using an ultrasonic pumping system, a size-selective cyclone separator, and a filter. Filter measurements can be used to correct the output from a low-cost direct-reading PM2.5 sensor housed within the SPARC. AOD is measured using optically filtered photodiodes at four discrete wavelengths. A suite of integrated sensors enable time-resolved measurement of key metadata including location, altitude, temperature, barometric pressure, relative humidity, solar incidence angle and spatial orientation. The AOD sensors were calibrated relative to a reference monitor in the Aerosol Robotics Network (AERONET). Field validation studies revealed close agreement for AOD values measured between co-located SPARC and AERONET monitors and for PM2.5 mass measured between co-located SPARC and EPA Federal Reference Method (FRM) monitors. These field validation results for this novel monitor demonstrate that AOD and PM2.5 can be accurately measured for the evaluation of AOD:PM2.5 ratios.